Aplikasi Edukasi Pembelajaran Interaktif Alfabet Anak menggunakan Teknologi Augmented Reality - Rahadian Fernandika; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Alphabet recognition learning can be developed with these technological advances, namely by using Augmented Reality technology as an interactive learning media for the introduction of the alphabet. Based on previous research, the author wants to provide a solution by making an application to solve the problem of a child's lack of interest in learning. Then the application created will be added with images as examples of using the alphabet so that children are more interested in learning to use the application. Recognition of the letters of the alphabet is one of the skills of children who develop from an early age, especially kindergarten children, namely language skills. The child's ability to recognize the alphabet is indicated by the child's ability to pronounce the sounds and names for each alphabet. The application testing uses methods, namely Blackbox Testing and Smileyometer, the Blackbox method tests the functionality aspects of an application and testing uses a Smileyometer to assess user experience when using the application. The results of the Blackbox Testing all test results run according to their functions and the Smileyometer test results in the Pre-test get an average value of 3.4 and the Post-test gets a value of 4.5 from these results it can be concluded that the application can increase children's interest in learning the alphabet.